Detection of carbapenemase-producing carbapenem resistant Enterobacterales (CP-CRE): A preliminary data from a tertiary hospital in Malaysia - Dr Fairuz Abdul Rashid; Dr Noraziah Sahlan; Associate Professor Dr Navindra Kumari Palanisamy; Dr Siti Farah Nawi; Associate Professor Dr Fadzilah Mohd Nor (International Journal of Infectious Diseases)
Introduction: Infection with carbapenem resistant Enterobacterales (CRE) is a public health concern associated with significant morbidity and mortality rates due to limited effective antibiotics available. Production of carbapenemase is the principal mechanism of carbapenem resistance in Enterobacterales. To date, there is limited local data available leading to a substantial knowledge gap on carbapenemase-producing carbapenem resistant Enterobacterales (CP-CRE). Thus, the study aimed to genotypically characterize the CRE isolates by detecting carbapenemase-producing genes via polymerase chain reaction (PCR) and CP-CRE genes association with antimicrobial susceptibility testing (AST) profile. Methods: A total of 375 Enterobacterales were isolated from sterile and non-sterile specimens in Hospital Kuala Lumpur, Malaysia from August 2023 to February 2024. Of these, 66 (17.6%) isolates exhibited phenotypic resistance to at least one carbapenem (meropenem/imipenem/ertapenem) by E-test. These isolates were subjected to multiplex conventional PCR to determine the presence of CRE genes including blaNDM, blaOXA-48, blaIMP, blaKPC and blaVIM. Moreover, the AST pattern of CRE isolates were analysed. Results & Discussion: All 66 isolates were mainly recovered from general wards; 47 (71.2%), intensive care unit; 16 (24.2%) and outpatients; 3 (4.5%). Urine (36.4%) and blood cultures (22.7%), contributed as the major source of Enterobacterales respectively, followed by tracheal aspirate (15.2%), pus swab (6.1%) and sputum (6.1%). The most common isolates were Klebsiella spp.; 34 (51.5%), Enterobacter spp.; 18 (27.3%) and Escherichia coli; 9 (13.6%). The PCR revealed 41 (62.1%) isolates harboured at least one or a combination of CP-CRE genes. The blaNDM (78%) was the most prevalent single gene detection in 32 isolates (16 Klebsiella spp., 8 Enterobacter spp., 6 E. coli and 2 others) with 2 of the isolates co-harboured blaVIM (4.9%). Other CP-CRE genes detected were blaOXA-48; 4 (9.8%) and blaKPC in 3 isolates (7.3%), with 2 of the isolates co-harboured blaKPC and blaIMP (4.9%). Two isolates harboured blaIMP (2.4%) and blaKPC (2.4%) each respectively. Antimicrobial susceptibility profile of the CP-CRE isolates showed susceptibility to the following β-lactam agents: cefepime; 5 (12.2% include 2 co-blaKPC and blaIMP, 2 blaNDM and 1 blaOXA-48), cefoperazone; 4 (9.8% includes 2 blaKPC and blaIMP, 1 blaIMP and 1 blaNDM), and ceftazidime; 4 (9.8% includes 2 blaKPC and blaIMP, 1 blaIMP and 1 blaNDM). Among the non-beta lactam agents tested against these isolates were amikacin and gentamicin which showed 26.8% and 24.4% susceptibility respectively, providing greater incremental coverage as second agents, compared to ciprofloxacin which demonstrated 14.6% susceptibility. Trimethoprim-sulfamethoxazole and nitrofurantoin, potential anti-CRE agents for urinary tract infection, demonstrated 22% and 35.5% susceptibility respectively. Conclusion: The blaNDM is the most predominant CP-CRE gene mainly isolated from Klebsiella spp. with diverse AST profile remains evident. These preliminary data may serve as an initial guide towards a tailored management of CP-CRE infections in our setting.